PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK KELAS VIII SMPN 3 PARIAMAN - EKA WIDYANINGSIH (Departemen Matematika, 2020)
Based on observations in class VIII SMPN 3 Pariaman, it was found that students’ mathematical reasoning abilities were still low. One of the reasons is the learning applied is not optimal training and improving mathematical reasoning skill well. Efforts that can be used are implementing DL models. The purpose of this study is to determine and discribe whether the ability of mathematical reasoning learning with the application of DL models is better thanthe ability to solve mathematical reasoning by applying the conventional learning. This type of research is quasy experimental research design with Randomized Control Group Only Desain. The study population was students of class VIII SMPN 3 Pariaman with a sample of class VIII 6 and VIII 7. The instrument used was a test of mathematical reasoning abilities in the form of essay questions. The results showed the ability to solve mathematical reasoning with the application of DL models is better thanthe ability to solve mathematical reasoning with the application of direct conventional learning.Keywords — Discovery Learning (DL), reasoning skill, Mathematics